Factors in B cell competition and immunodominance. Issue 1 (1st June 2020) - Abbott, Robert K.; Crotty, Shane
Abstract: The majority of all vaccines work by inducing protective antibody responses. The mechanisms by which the B cells responsible for producing protective antibodies are elicited to respond are not well understood. Interclonal B cell competition to complex antigens, particularly in germinal centers, has emerged as an important hurdle in designing effective vaccines. This review will focus on recent advances in understanding the roles of B cell precursor frequency, B cell receptor affinity for antigen, antigen avidity, and other factors that can substantially alter the outcomes of B cell responses to complex antigens. Understanding the interdependence of these fundamental factors that affect B cell responses can inform current vaccine design efforts for pathogens with complex proteins as candidate immunogens such as HIV, influenza, and coronaviruses.